PENENTU BEBERAPA KOMPONEN TERHADAP KUALITAS LAPORAN KEUANGAN - La Ode Hasiara; Amiril Azizah (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2023)
The aim of this research is to investigate the quality of financial reports that are influenced by some elements. The research method uses a quantitative approach to multiple linear regression models. The results showed that the competence of auditors, independence of auditors, standard operating procedures, information technology, and accounting standards have positive and significant effects on the quality of financial statements. In conclusion, all independent variables both simultaneously and partially have a positive and significant effect on the quality of financial statements.